1984
DOI: 10.1007/bf01451523
|View full text |Cite
|
Sign up to set email alerts
|

Solution properties of mixed surfactant systems (IV)

Abstract: Electric properties of mixed anionic-nonionic surfactant systems in aqueous solutions above the CMC have been studied in terms of pNa values, electrical conductivities, and dielectric constants; these systems are sodium 3, 6, 9-trioxaicosanoate (ECL)alkyl polyoxyethylene ethers (CmPOE; m---12,14,16, and 18). The degree of ionic dissociation of mixed micelle increases with increasing the number of carbon atoms of the alkyl group in the nonionic surfactant. The electrical conductivity increases with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The activity (a) of counter ion (Na +) in a surfactant solution can be expressed by the following Equation, suggested by Botre et al [29]: a = r" {Co + a. (c -c0)) (13) where y is the activity coefficient of the counterion (Na § a, the degree of ionic dissociation of micelle, Co, the CMC, and C, the concentration of SDS.…”
Section: Estimation Of Aggregation Number For Sodium Alkyl Sulfatesmentioning
confidence: 99%
“…The activity (a) of counter ion (Na +) in a surfactant solution can be expressed by the following Equation, suggested by Botre et al [29]: a = r" {Co + a. (c -c0)) (13) where y is the activity coefficient of the counterion (Na § a, the degree of ionic dissociation of micelle, Co, the CMC, and C, the concentration of SDS.…”
Section: Estimation Of Aggregation Number For Sodium Alkyl Sulfatesmentioning
confidence: 99%
“…chains than by one having shorter alkyl chains [18,20]. We have also reported that the mixed micelle is easier to form for a nonionic surfactant including shorter polyoxyethylene chains than for one including longer chains [16,21].…”
Section: Effect Of Alkyl Chain Length or Oxyethylene Chain Length On mentioning
confidence: 88%
“…We have also reported the solution properties of anionic-nonionic mixed surfactant systems obtained from electrical [16][17][18] and surface tension measurements [19][20][21], and have investigated the mixed micelle formation. We found that two kinds ofmicelles would form more easily in hydrocarbon-hydrocarbon mixed surfactant solutions with decreasing alkyl chain length and/or with increasing polyoxyethylene chains in nonionic surfactant.…”
Section: Introductionmentioning
confidence: 98%
“…The fading rate of 4-OH accelerated with increasing the alkyl chain length or with decreasing the oxyethylene chain length in the nonionic surfactant molecule. The effect on it was larger for a system which could easily form a mixed micelle than for a system in which two kinds of micelles coexisted [9][10][11]. A singlet oxygen, which is caused by the hydrophilic-hydrophilic interaction when the two surfactants were mixed, is thought to attack the hydrazo form (tautomer) of 4-OH.…”
Section: Introductionmentioning
confidence: 94%